Discussion (Scottish Historical and Archaeological Internet Reports, 2012)
The various categories of evidence already reported are brought together in a discussion of the cremation rite. The evidence indicates that early Bronze Age cremations were a complex mixture of funerary rites which hint at a complex social structure or set of beliefs, taboos and societal norms. It is currently the most comprehensively dated cremation cemetery in Britain and was in use from 2040-1500 BC.